Analisis Efek Komunitas dan Electronic Word Of Mouth terhadap Brand Switching Produk Xiaomi Pocophone ke Oppo F9 di RNY Communication Kota Sukabumi - Ackbar Pirdaus; R. Deni Muhammad Danial; Asep M. Ramdan (IPM2KPE, 2020)
The purpose of this study was to determine the effect of community and electronic word of mouth (e-WOM) on brand switching. The method used in this study is the method of sampling type included in the sample random sampling by distributing questionnaires as many as 150 to consumers. This research analysis technique uses multiple linear analysis techniques, and in testing the hypothesis using partial statistical tests (t test) and simultaneous tests (f test). T test results showed that the community effect (X1) had a significant effect on brand switching, electronic word of mouth (e-WOM) (X2) had a significant effect on brand switching. Based on the F test in this study the probability value sig 0,000 <0.05 while the coefficient of determination test of 0.818. Conclusions, community effects and electronic word of mouth (e-WOM) have a significant effect on brand switching. The effect of community effects and electronic word of mouth (e-WOM) on brand switching is 81.7%. The remaining 18.3% is influenced by other factors not explained in this study. Keywords: Brand switching, Community effects, Electronic word of mouth (e-WOM)